Kyai’s Leadership Model in Managing the Al-Khairat Islamic Boarding School, Gorontalo City - Mahmud, Wulandari; Kango, Andries; Panigoro, Muh. Rifian; Husain, Rahmin T.; Perdana, Dian Adi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This study aims to examine the Kyai’s leadership model in the management of the Al-Khairat Islamic Boarding School in Gorontalo City. It also seeks to explore the impact of Kyai’s leadership approach on the administration of the Al-Khairat Islamic Boarding School in Gorontalo City. Employing field research, this investigation endeavors to delineate the realities of Kyai’s leadership model at the Al-Khairat Islamic Boarding School in Gorontalo. The research was conducted on-site at the Al-Khairat Islamic Boarding School, utilizing observational methods, interviews, and document analysis to gather data. The process involved the collection of diverse information, which was subsequently refined by sorting through the data to deduce conclusive findings. The research reveals that the Kyai’s management of the Al Khairat Islamic Boarding School in Gorontalo City is underpinned by a clear vision and mission to develop the institution. It emphasizes the importance of Ahlussunnah wal Jama’ah Islam as a foundation for ethics, morality, motivation and inspiration for the students. Furthermore, it cultivates Alkhlakul karimah in students, aspiring to nurture a generation steeped in Rabbani values. The study identifies several leadership models employed by the Kyai, including visionary, charismatic, situational, and participative leadership. Significantly, the Kyai’s leadership is found to have a beneficial impact on educating students to become the next generation of Muslims leaders, equipped to enlighten their religion as rahmatan lil alamin.